The impact of nutritional availability in the microenvironment on metabolic reprogramming and aggressiveness of breast cancer cells - Esteves, Sofia Andreia Mata da Nazaré Pinheiro (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021